The Reaction to Fire Tests for Natural Thermal Insulation of Hemp Material Modified by Fire Retardant Ohnostop Special - Adelaida Fanfarova; Ladislav Maris; Anton Osvald; Esko Mikkola (Communications - Scientific letters of the University of Zilina, 2015)
The scope of the paper is the experiment focused on testing and evaluating the fire protection of fire retardant modification of combustible material by means of experimental scientific method of the reaction to fire test. We tested the specimens of natural thermal insulation made of hempen fibre provided by the company Profi air color s.r.o. Zilina. These tested specimens were impregnated with retardation technology by soaking in the fire retardant Ohnostop special, provided by the company Bakra s.r.o. Rimavska Sobota. The experiment was performed by two experimental methods - the single-flame source test and the test of limited flame spread with the test devices under laboratory conditions. The main aim of the experiment was the assessment and possible improvement of fire-technical properties of thermal insulation material made of hemp by the application of fire retardant modification.